2019
DOI: 10.1200/edbk_238353
|View full text |Cite
|
Sign up to set email alerts
|

Management for Different Glioma Subtypes: Are All Low-Grade Gliomas Created Equal?

Abstract: Following the identification of key molecular alterations that provided superior prognostication and led to the updated 2016 World Health Organization (WHO) Central Nervous System (CNS) Tumor Classification, the understanding of glioma behavior has rapidly evolved. Mutations in isocitrate dehydrogenase (IDH) 1 and 2 are present in the majority of adult grade 2 and 3 gliomas, and when used in conjunction with 1p/19q codeletion for classification, the prognostic distinction between grade 2 versus grade 3 is dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 146 publications
1
63
0
Order By: Relevance
“…Depending on the speed and extent of tumor growth, histological features and tumor invasiveness, gliomas have been graded by the World Health Organization (WHO) between Grades I and IV [ 125 , 126 ]. Low-grade gliomas (Grade II–III) include astrocytomas and oligodendrogliomas [ 126 , 127 ], while the most common type of higher grade glioma is an astrocytoma known as glioblastoma (GBM) [ 124 ].…”
Section: Role Of Tumor-derived Evs In Gliomamentioning
confidence: 99%
“…Depending on the speed and extent of tumor growth, histological features and tumor invasiveness, gliomas have been graded by the World Health Organization (WHO) between Grades I and IV [ 125 , 126 ]. Low-grade gliomas (Grade II–III) include astrocytomas and oligodendrogliomas [ 126 , 127 ], while the most common type of higher grade glioma is an astrocytoma known as glioblastoma (GBM) [ 124 ].…”
Section: Role Of Tumor-derived Evs In Gliomamentioning
confidence: 99%
“…The optimal use of targeted therapy in brain tumors remains under investigation, and its efficacy in lowgrade tumors, which would conceivably be slow growing, has been difficult to assess [72]. Although detection of these possible therapeutic targets is of great clinical interest, high quality clinical data remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the wide range of patients' survival within each grade, the evaluation results of the classic TNM classification are not entirely satisfactory. In recent years, with the in-depth research in molecular biology, scientists have found that IDH 1 and 2 mutations and 1p/19q codeletion play a more important role than TNM stage in the prognosis of glioma patients (1,2). In 2016, the WHO made a major change in the classification of gliomas, incorporating molecular characteristics into the classification (3).…”
Section: Introductionmentioning
confidence: 99%